Differences in gut microbiome between autosomal dominant polycystic kidney disease with and without intracranial aneurysms - Tatsumaru Fukuda; Masatoshi Takagaki; Junya Kaimori; Daisuke Motooka; Shota Nakamura; Shuhei Kawabata; Hajime Nakamura; Tomohiko Ozaki; Ryota Nakagawa; Takaki Matsumura; Kunimasa Teranishi; Hiroki Yamazaki; et al. (Scientific Reports)
Abstract Autosomal dominant polycystic kidney disease (ADPKD) is a genetic disorder characterized by cyst formation in the kidneys, and is associated with an elevated risk of intracranial aneurysms (IAs). Although a family history is a recognized risk factor for IAs in patients with ADPKD, emerging research suggests that gut microbiome composition may influence IA development. We investigated the relationship between the gut microbiome and the development of IA in patients with ADPKD. We recruited patients with ADPKD with (IA group) and without (non-IA group) IA from Osaka University between October 2021 and December 2023. Fecal samples were analyzed using 16S rRNA sequencing. Data were processed using the QIIME 2 pipeline to determine microbial diversity and composition. We included 60 patients: 26 in the IA and 34 in the non-IA groups. There were significant differences in microbial beta diversity between the groups. The IA group had higher abundances of Eubacterium siraeum group, Oscillibacter, Fournierella, Negativibacillus, Colidextribacter, and Adlercreutzia. The non-IA group had higher abundances of Bifidobacterium, Megamonas, Acidaminococcus, Megasphaera, and Merdibacter. There was a significant association between the gut microbiome composition and the presence of IAs in patients with ADPKD. Specific bacterial taxa were differentially abundant between patients with ADPKD with and without IAs, suggesting a potential role of the gut microbiome in the pathogenesis of IAs in this genetically predisposed population.